European Union Work-Life Balance Directive: A Lesson for Indonesia - Rofi Aulia Rahman; Aimee Joy David; Jumi Apriza; József Hajdú (Varia Justicia, 2022)
The aim of this article is to compare the legal development of the work-life balance directive in the European Union (EU) and Indonesia. The objective of the Work-Life Balance Directive is to enhance the existing EU legal framework for family-related leave and flexible work arrangements. The directive includes the introduction of paternity leave (the equivalent second parent/parent will be able to take at least 10 working days of maternity leave around the birth of the child, compensated at least at the rate of sick pay); the strengthening of the right to leave for birth for 4 months and the right to request flexible leave (e.g., part-time or gradually); and the establishment of nursing leave (5 days/year) for workers caring for permanency-impaired relatives. This policy can serve as a model for Indonesia in terms of defending worker rights and promoting a healthy work-life balance. Nonetheless, the Indonesian legal framework governing the work-life balance remains obscure. Therefore, the Indonesian legal system must modify existing regulations and/or pass new laws to ensure the quality of working time and life are balance which gradually could impact to the families economic stability.